Hubungan Tingkat Stres Dengan Tingkat Perilaku Merokok Pada Mahasiswa Semester Tujuh Di Fakultas Hukum Universitas Muhammadiyah Surakarta - Aulia Putri, Risda (2016)
Background. Smoking behavior has been widespread among the Indonesian people. The number of smokers did not experience a decline over the years; instead, it has been increasing. One of the causes of smoking behavior is stress. Stress is defined as a person's self-adjustment effort to internal and external physiological and psychological demands. Objective. To analyze a relationship between stress level and smoking behavior level of seventh-semester students at the Faculty of Law of Muhammadiyah University of Surakarta. Methods. This study is an observational analytical design with cross-sectional approach. Forty seven students were drawn by purposive sampling technique. Pearson correlation test was employed as the statistical test. Results. The study found an r value of 0.421, which means stress level and smoking behavior level have a moderate level of correlation, and p value of 0.003, indicating a significant relationship between stress level and smoking behavior level as well as a tendency to positive correlation. Conclusion. There is a relationship between stress level and smoking behavior level and the higher the stress level is, the higher the smoking behavior will be. Keywords: Stress level, smoking behavior level, stress among students, smoking behavior among students. ¹Student at Faculty of Medicine, Muhammadiyah University of Surakarta ²Lecturer at Faculty of Medicine, Muhammadiyah University of Surakarta